Constructing narrative identity through memoir writing: A narrative inquiry of self-publishing young adults - Fakhirah Inayaturrobbani (Academic Journal of Psychology and Counseling, 2026)
Despite extensive research on narrative and identity, previous studies tend to focus either on narrative as a textual product or on lived experience, with limited attention to memoir writing as an active process of identity construction. Therefore, this study aims to examine how young adult indie authors construct identity through the process of memoir writing. Using a narrative inquiry approach, this study investigates three self-published memoir authors (aged 20–25) through in-depth narrative interviews. Data were analyzed using thematic analysis and a chronological narrative framework. The finding shows that narrative identity construction in memoir writing is a dynamic and staged process in which individuals engage with difficult life experiences to create meaning, regulate emotions, and develop a coherent sense of self. It further demonstrates that this process is shaped not only by internal reflection but also by social relationships and digital writing environments. Practically, digitally mediated memoir writing can be used as a structured reflective practice in youth development programs and psychosocial support settings to help young adults construct a more coherent sense of identity